Oxide electrolyte-negative electrode interface modification layer, solid-state lithium battery and preparation method of solid-state lithium battery
By forming an interface modification layer between the porous support layer and the in-situ filling layer between the oxide electrolyte and the negative electrode, the problems of the difference in interface contact between the oxide electrolyte and the electrode and the growth of the lithium negative electrode dendrites are solved, and the stable transmission of lithium ions is achieved And battery cycle stability improves.
Patent Information
- Application Number
- CN202411275153.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-12
- Publication Date
- 2024-12-20
AI Technical Summary
There are problems in the oxide-based solid lithium battery with poor contact between the oxide electrolyte and the electrode interface, growth of lithium negative electrode dendrites and side reactions of the electrolyte/negative electrode interface, resulting in insufficient battery stability.
The oxide electrolyte-negative electrode interface modification layer is combined with a porous support layer and an in-situ fill layer. The porous support layer is formed in humid air through a polymer solution, and an ether-based monomer, a plasticizer, an initiator, and a lithium salt are used. The polymerization precursor is wet and cured to form an in-situ fill layer to improve interface contact and stability.
Effectively isolate the direct contact between oxides and lithium negative electrodes, promote rapid transmission of lithium ions, inhibit dendrites' growth and side reactions, and improve the cycle stability and energy density of the battery.
Smart Images

Figure CN119170858A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of solid-state lithium batteries, and in particular relates to an oxide electrolyte-negative electrode interface modification layer, a solid-state lithium battery and a preparation method thereof. Background Art
[0002] In recent years, lithium-ion batteries have been widely used in consumer electronics, electric vehicles, energy storage power stations and other fields due to their advantages such as high energy density, long life and no memory effect. After many technical iterations, the energy density of lithium-ion batteries has gradually reached a bottleneck (it is difficult to exceed 300Wh / kg), and it is gradually difficult to meet people's further demand for energy density. In addition, lithium-ion batteries contain a large amount of organic electrolytes. When the battery is thermally runaway due to force majeure, it is very easy to burn or even explode, which greatly reduces people's desire to consume it. Solidification of electrolytes is considered to be the ultimate direction to solve the problem. On the one hand, solid electrolytes have excellent thermal stability and can solve safety problems at the intrinsic level; on the other hand, solid electrolytes can be compatible with high-energy positive and negative electrode materials at the same time after reasonable design, thereby achieving ultra-high energy density. Among the many solid-state battery technology routes, oxide electrolytes have received widespread attention from all walks of life in recent years due to their advantages such as high intrinsic thermal stability, high ionic conductivity and wide electrochemical window. However, due to the inherent hardness of oxide materials, direct bonding with electrodes will result in poor physical contact, and some materials will also have some irreversible side reactions when in contact with electrodes.
[0003] In order to alleviate the above defects, a variety of modification methods have been proposed. Patent CN116799290A discloses a garnet-type oxide electrolyte based on surface Li2CO3, which converts Li2CO3 into Li with high ionic conductivity through the co-firing reaction of amino acid. x B y O z , which is essentially an inorganic modified layer, still has the problem of poor interface contact, and this method is not universal and is not suitable for other oxide electrolytes without Li2CO3 surface. Patent CN114006033B discloses that a layer of PVDF-HFP and LiTFSI salt-encapsulated polymer organic interface layer is modified on the surface of NASICON-type LATP electrolyte. The organic interface layer improves the interface contact to a great extent, but due to the thick interface layer and poor ionic conductivity, the battery still needs to operate at 60°C.
[0004] Based on this, there is an urgent need to develop a thin, flexible, fast ion-transmitting, and universal interface layer to improve the interface contact between the oxide electrolyte and the electrode, while being able to inhibit the growth of negative electrode dendrites and reduce electrolyte / negative electrode interface side reactions, thereby achieving stable and long-term performance of oxide-based solid-state batteries. Summary of the invention
[0005] In view of the technical problems existing in the above-mentioned oxide-based solid-state batteries, such as poor electrolyte / electrode interface contact, lithium negative electrode dendrite growth, electrolyte / lithium negative electrode interface side reactions, etc., the purpose of the present invention is to provide an oxide electrolyte-negative electrode interface modification layer, a solid-state lithium battery and a preparation method thereof.
[0006] In a first aspect, the present invention provides an oxide electrolyte-negative electrode interface modification layer, wherein the oxide electrolyte-negative electrode interface modification layer is located between the oxide electrolyte and the negative electrode and is composed of a porous support layer and an in-situ filling layer; in: The porous support layer is formed by a low boiling point solvent in a polymer solution dripped onto the surface of the oxide electrolyte through non-solvent phase separation with moisture in humid air at a relative humidity of >80% RH on the surface of the solution; The in-situ filling layer is formed by infiltrating the porous support layer with a polymerization precursor liquid containing an ether monomer, a plasticizer, an initiator, and a lithium salt and then curing it in-situ.
[0007] Preferably, the porous support layer has a pore size of 0.1-10 μm, preferably 1-5 μm, and a porosity of 30-70%, preferably 40-60%; the thickness of the oxide electrolyte-negative electrode interface modification layer is 2-10 μm, preferably 3-6 μm.
[0008] Preferably, based on the total mass of the oxide electrolyte-negative electrode interface modification layer being 100%, the mass of the porous support layer accounts for 30-50%, and the mass of the in-situ filling layer accounts for 50-70%.
[0009] Preferably, the ionic conductivity of the oxide electrolyte-negative electrode interface modification layer is not less than 10 -4 S / cm.
[0010] Preferably, the polymer used to prepare the porous support layer is at least one of polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene, polymethyl methacrylate, and polyacrylonitrile, preferably at least one of polyvinylidene fluoride and polyvinylidene fluoride-hexafluoropropylene; The low boiling point solvent is at least one of acetone, tetrahydrofuran, xylene, diethyl ether and acetonitrile, preferably at least one of acetone and tetrahydrofuran.
[0011] Preferably, the ether monomer contained in the polymerization precursor solution for preparing the in-situ filling layer is at least one of 1,3-dioxolane, 1,3-dioxane, trioxymethylene, and tetrahydrofuran, preferably 1,3-dioxolane; The plasticizer is at least one of fluoroethylene carbonate, dimethyl carbonate, ethyl methyl carbonate, diethyl carbonate, and propylene carbonate, preferably fluoroethylene carbonate; The initiator is at least one of zinc trifluoromethanesulfonate, tin trifluoromethanesulfonate, magnesium trifluoromethanesulfonate, scandium trifluoromethanesulfonate, and aluminum trifluoromethanesulfonate, preferably zinc trifluoromethanesulfonate; The lithium salt is at least one of lithium bis(trifluoromethanesulfonyl imide), lithium bis(pentafluoroethylsulfonyl imide) and lithium trifluoromethanesulfonate, preferably lithium bis(trifluoromethanesulfonyl imide).
[0012] Preferably, the volume ratio of the ether monomer to the plasticizer is 99:1-50:50, preferably 80:20-55:45; the amount of initiator added is 1-10mM of the total volume of the ether monomer and the plasticizer, preferably 3-9mM; the amount of lithium salt added is 0.5-2M of the total volume of the ether monomer and the plasticizer, preferably 0.8-1.2M.
[0013] Preferably, the oxide electrolyte is at least one of NASICON-type oxide, garnet-type oxide, and perovskite-type oxide; The NASICON-type oxide includes Li 1+x Al x M 2-x (PO4)3、Li 1+x+y Al x M 2-x Si y P 3-y O 12 , M is Ti or Ge, 0≤x≤0.5, 0≤y≤0.5, preferably Li 1+x Al x Ti 2-x (PO4)3, 0.2≤x≤0.4; The garnet-type oxide includes Li 7-x Ln3Z 2-x N x O 12 , N is Nb, Sb or Ta, 0≤x≤0.8, preferably Li 7-x Ln3Z 2-x Ta x O 12 , 0.4≤x≤0.6; The perovskite oxide includes Li 3x La 2 / 3-x TiO3, 0.06≤x≤0.14, preferably x=0.11.
[0014] In a second aspect, the present invention provides a method for preparing an oxide electrolyte-negative electrode interface modification layer, the preparation method comprising the following steps: (1) dissolving a polymer in a low boiling point solvent to form a polymer solution and dripping it onto the surface of the oxide electrolyte, wherein the polymer solution is separated from water by a non-solvent phase in humid air at a relative humidity of more than 80% RH, and then dried to obtain a porous support layer; (2) An ether monomer, a plasticizer, an initiator, and a lithium salt are mixed to form a polymerization precursor solution, and the mixture is dripped into the porous support layer to wet the pores thereof, and the mixture is allowed to stand at room temperature under sealing conditions to perform in-situ curing to form an in-situ filling layer of a gel electrolyte, thereby obtaining the oxide electrolyte-negative electrode interface modification layer.
[0015] In a third aspect, the present invention provides a solid-state lithium battery, comprising a positive electrode, a negative electrode, an oxide electrolyte, and the oxide electrolyte-negative electrode interface modification layer; After modifying the porous support layer on one side of the oxide electrolyte, the polymerization precursor liquid of the in-situ filling layer is injected into the porous support layer, the negative electrode is attached, and the polymerization precursor liquid is dripped on the other side of the oxide electrolyte, the positive electrode is attached, sealed, and left to stand at room temperature to obtain the solid-state lithium battery.
[0016] Beneficial Effects The porous polymer support layer in the modified interface layer provided by the present invention can effectively isolate the direct contact between the oxide and the lithium negative electrode, reducing the reduction side reaction at the thermodynamic level; the in-situ filling layer in the modified interface layer has a precursor liquid with a relatively low viscosity, which can fully wet the interface, and after being cured by an initiator, can achieve excellent stability to the lithium negative electrode, while ensuring the rapid and stable transmission of ions on the interface; after being assembled into a battery, the interface modification layer can effectively improve the cycle stability of the oxide-based solid-state lithium battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] Figure 1 The figure is a schematic diagram of a method for preparing an oxide electrolyte-negative electrode interface modification layer according to an example of the present invention; Figure 2 This is a SEM image of the porous polyvinylidene fluoride support layer modified on the surface of the electrolyte sheet in Example 1; Figure 3 Optical photographs of the in-situ filling layer polymerization precursor liquid used in Example 1 before and after curing; Figure 4 This is a test diagram of the cycle performance of solid-state lithium batteries assembled in Example 1, Comparative Example 1, and Comparative Example 2. DETAILED DESCRIPTION
[0018] The present invention is further described below by the following embodiments. It should be understood that the following embodiments are only used to illustrate the present invention, but not to limit the present invention.
[0019] First, the present invention provides an oxide electrolyte-negative electrode interface modification layer. Specifically, the oxide electrolyte-negative electrode interface modification layer is located between the oxide electrolyte and the negative electrode, and is composed of a porous support layer and an in-situ filling layer; wherein: The porous support layer can be formed by a polymer solution dripped onto the surface of the oxide electrolyte in humid air (>80% RH) through non-solvent phase separation between a low boiling point solvent and moisture in the air on the surface of the solution; The in-situ filling layer can be formed by infiltrating the porous support layer with a polymerization precursor solution containing an ether monomer, a plasticizer, an initiator, and a lithium salt, followed by in-situ curing.
[0020] In the oxide electrolyte-negative electrode interface modification layer provided by the present invention, the porous support layer mainly plays the role of physically isolating the oxide electrolyte / negative electrode, preventing the two from directly contacting and causing possible side reactions. The in-situ filling layer has high ionic conductivity and good alkali metal compatibility, and mainly plays the role of promoting interfacial lithium ion transmission and ensuring electrochemical performance; at the same time, the polymer phase used in the in-situ filling layer of the present invention is an ether-based polymer, which has good compatibility with the lithium negative electrode, can guide the uniform deposition of lithium, and inhibit the growth of lithium dendrites, and the filling layer formed by the in-situ polymerization process can also greatly simplify the process flow of constructing a solid-state lithium battery.
[0021] In some embodiments, the porous support layer may have a pore size of 0.1-10 μm, preferably 1-5 μm, and a porosity of 30-70%, preferably 40-60%. Too small pore size and porosity are not conducive to infiltration, while too large pore size and porosity will weaken its physical isolation ability.
[0022] In some embodiments, based on the total mass of the oxide electrolyte-negative electrode interface modification layer being 100%, the mass proportion of the porous support layer may be 30-50%, and the mass proportion of the in-situ filling layer may be 50-70%.
[0023] In some embodiments, the thickness of the oxide electrolyte-negative electrode interface modification layer may be 2-10 μm, preferably 3-6 μm. The thickness of the interface modification layer is mainly determined by the porous support layer. Too small a thickness may cause defects in the porous support layer, while too large a thickness may be detrimental to ion transport.
[0024] In some embodiments, the ionic conductivity of the oxide electrolyte-negative electrode interface modification layer is not less than 10 - 4 S / cm.
[0025] In summary, the oxide electrolyte-negative electrode interface modification layer provided by the present invention has the characteristics of thin thickness, good flexibility, high ionic conductivity, etc., which can effectively improve the interface physical contact between the oxide electrolyte and the electrode, ensure the stable and rapid transmission of lithium ions at the interface, and inhibit the growth of lithium dendrites and various irreversible side reactions at the electrolyte / lithium negative electrode interface, thereby improving the cycle life of the oxide-based electrolyte solid-state battery.
[0026] The following, combined Figure 1 , exemplarily illustrating the preparation method of the oxide electrolyte-negative electrode interface modification layer provided by the present invention. Wherein, the preparation method may include the following steps: (1) dissolving a polymer in a low boiling point solvent to form a polymer solution and dripping it onto the surface of the oxide electrolyte, wherein the polymer solution is separated from water by a non-solvent phase in humid air at a relative humidity of more than 80% RH, and then dried to obtain a porous support layer; (2) An ether monomer, a plasticizer, an initiator, and a lithium salt are mixed to form a polymerization precursor solution, and the mixture is dripped into the porous support layer to wet the pores thereof, and the mixture is allowed to stand at room temperature under sealing conditions to perform in-situ curing to form an in-situ filling layer of a gel electrolyte, thereby obtaining the oxide electrolyte-negative electrode interface modification layer.
[0027] In some embodiments, in step (1), the oxide electrolyte may be at least one of a NASICON-type oxide, a garnet-type oxide, and a perovskite-type oxide. The NASICON-type oxide may include Li 1+ x Al x M 2-x (PO4)3、Li 1+x+y Al x M 2-x Si y P 3-y O 12 , M is Ti or Ge, 0≤x≤0.5, 0≤y≤0.5, preferably Li 1+ x Al x Ti 2-x (PO4)3, 0.2≤x≤0.4; the garnet-type oxide may include Li 7-x Ln3Z 2-x N x O 12 , N is Nb, Sb or Ta, 0≤x≤0.8, preferably Li 7-x Ln3Z 2-x Ta x O 12 , 0.4≤x≤0.6; the perovskite oxide may include Li 3x La 2 / 3-xTiO3, 0.06≤x≤0.14, preferably x=0.11.
[0028] The oxide electrolyte may be in the shape of a disc, with a thickness of 0.1-1.5 mm, preferably 0.5-1.1 mm; and a diameter of 8-15 mm, preferably 9-12 mm.
[0029] In some embodiments, in step (1), the polymer may be at least one of polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene, polymethyl methacrylate, and polyacrylonitrile, preferably at least one of polyvinylidene fluoride and polyvinylidene fluoride-hexafluoropropylene.
[0030] In some embodiments, in step (1), the low boiling point solvent may be at least one of acetone, tetrahydrofuran, xylene, diethyl ether, and acetonitrile, preferably at least one of acetone and tetrahydrofuran.
[0031] The polymer solution is dripped onto the surface of the oxide sheet, and the solvent in the solution undergoes non-solvent phase separation with the moisture in the humid air (>80% RH) on the surface of the solution to form pores. In some embodiments, in step (1), the non-solvent phase separation time is at least 1 hour, preferably 1-2 hours.
[0032] Different from the non-solvent phase separation process of the coagulation bath method in which the pore-forming process is too intense, the present invention utilizes low-boiling point solvents and moisture in humid air (>80% RH) for non-solvent phase separation, which is a gentle pore-forming method and is more suitable for directly preparing thin, tightly fitting porous membranes on the surface of electrolyte sheets.
[0033] In some embodiments, in step (1), the drying process can be: drying in a vacuum drying oven at 50-90° C. for at least 12 h, preferably drying in a vacuum drying oven at 60-80° C. for 12-24 h.
[0034] In some embodiments, in step (1), the thickness of the porous support layer may be 2-10 μm, preferably 3-6 μm.
[0035] In some embodiments, in step (2), the ether-based monomer may be at least one of 1,3-dioxolane, 1,3-dioxane, trioxymethylene, and tetrahydrofuran, preferably 1,3-dioxolane.
[0036] In some embodiments, in step (2), the plasticizer may be at least one of fluoroethylene carbonate, dimethyl carbonate, ethyl methyl carbonate, diethyl carbonate, and propylene carbonate, preferably fluoroethylene carbonate.
[0037] In some embodiments, in step (2), the initiator may be at least one of zinc trifluoromethanesulfonate, tin trifluoromethanesulfonate, magnesium trifluoromethanesulfonate, scandium trifluoromethanesulfonate, and aluminum trifluoromethanesulfonate, preferably zinc trifluoromethanesulfonate.
[0038] In some embodiments, in step (2), the lithium salt may be at least one of lithium bis(trifluoromethanesulfonyl imide), lithium bis(pentafluoroethylsulfonyl imide), and lithium trifluoromethanesulfonate, preferably lithium bis(trifluoromethanesulfonyl imide).
[0039] In some embodiments, in step (2), the volume ratio of the ether monomer to the plasticizer may be 99:1-50:50, preferably 80:20-55:45; the amount of initiator added may be 1-10 mM of the total volume of the ether monomer and the plasticizer, preferably 3-9 mM; the amount of lithium salt added may be 0.5-2 M of the total volume of the ether monomer and the plasticizer, preferably 0.8-1.2 M. The ether monomer is a polymer component, and the proportion of the polymer component is set to be greater than the plasticizer component to ensure a better degree of solidification after polymerization; the plasticizer is controlled within an appropriate range to ensure a higher ionic conductivity; too high an initiator concentration will result in a significant shortening of the polymerization time, which is not conducive to the smooth progress of the preparation process, and the ionic conductivity will be weakened; too low a concentration will cause a decrease in efficiency.
[0040] The formulation of pure ether monomers without plasticizers will result in low conductivity of the filler after polymerization and poor interface ion transport; in addition, unlike using lithium salts as initiators, the initiator used in the present invention is a trifluoromethanesulfonic acid initiator.
[0041] In some embodiments, in step (2), the amount of the polymerization precursor solution used may be 2-10 μL, preferably 3-6 μL.
[0042] In some embodiments, in step (2), the standing time at room temperature can be 12-48 hours, preferably 24 hours. In this process, the ether monomer will be ring-opened and polymerized into macromolecules under the initiator, and form a gel electrolyte under the action of the plasticizer.
[0043] In addition, the present invention also provides a solid-state lithium battery. The solid-state lithium battery includes a positive electrode, a negative electrode, an oxide electrolyte, and the oxide electrolyte-negative electrode interface modification layer; the positive electrode can be at least one of lithium iron phosphate, lithium manganese iron phosphate, nickel cobalt manganese ternary, lithium cobalt oxide, and lithium manganese oxide, and the negative electrode can be at least one of lithium metal, lithium indium alloy, lithium magnesium alloy, and lithium silver alloy.
[0044] The following is an exemplary description of the preparation method of the solid-state lithium battery provided by the present invention. The preparation method of the solid-state lithium battery may include the following steps: after modifying the porous support layer on one side of the oxide electrolyte, injecting the polymerization precursor liquid of the in-situ filling layer into the porous support layer, attaching the negative electrode, dripping the polymerization precursor liquid on the other side of the oxide electrolyte, attaching the positive electrode, sealing, and standing at room temperature (for example, at 25°C for 24 hours) to obtain the solid-state lithium battery.
[0045] The filling layer precursor solution can be used as an interface wetting agent on the positive electrode surface. In some embodiments, the capacity retention rate of the solid-state lithium battery can reach 92% after 400 cycles at 25°C and 0.5C.
[0046] The oxide electrolyte interface modification layer and the solid-state lithium battery assembled therein provided by the present invention, the interface modification layer is compositely synthesized by a porous support layer and an in-situ filling layer, the porous support layer is formed by dripping a polymer solution onto an oxide electrolyte sheet through non-solvent phase separation, the in-situ filling layer is formed by injecting a precursor solution of an ether-based monomer, a plasticizer, a lithium salt, and an initiator into the pores of the support layer through in-situ initiation by the initiator, the isolation layer avoids direct contact between the oxide electrolyte body and the lithium negative electrode to cause possible side reactions, the filling layer has high ionic conductivity and good stability to lithium, and ultimately achieves better interface adaptation between the oxide and the lithium negative electrode, thereby improving the cycle stability of the solid-state lithium-ion battery of the oxide-based electrolyte.
[0047] The following further examples are given to illustrate the present invention in detail. It should also be understood that the following examples are only used to further illustrate the present invention and cannot be construed as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made by those skilled in the art based on the above content of the present invention all belong to the scope of protection of the present invention. The specific process parameters of the following examples are also only examples within a suitable range, that is, those skilled in the art can make selections within a suitable range through the description of this article, and are not limited to the specific values exemplified below. If not specifically stated, the technical means used in the embodiments are conventional means well known to those skilled in the art.
[0048] Example 1
[0049] The preparation method of the oxide electrolyte-negative electrode interface modification layer and the solid-state lithium battery provided in this embodiment comprises the following steps: (1) Preparation of a porous supporting layer polymer solution: polyvinylidene fluoride and acetone were mixed at a polymer mass fraction of 5%, and stirred for 12 hours until completely dissolved to obtain the porous supporting layer polymer solution; Preparation of the in-situ filling layer polymerization precursor solution: 1,3-dioxolane and fluoroethylene carbonate were mixed in a volume ratio of 6:4, 1M lithium bis(trifluoromethanesulfonyl)imide and 8mM zinc trifluoromethanesulfonate were added and stirred evenly to obtain the in-situ filling layer polymerization precursor solution; (2) Solid-state batteries were assembled using CR2032 button cells as carriers. The porous support layer polymer solution was added dropwise to the oxide electrolyte Li 1.3 Al 0.3 Ti 1.7 The (PO4)3 surface (disk-shaped, 1 mm thick, 12.3 mm in diameter) was placed in humid air (>80% RH) for 1 h to allow it to fully undergo non-solvent phase separation with the moisture in the air, and then dried at 80°C in vacuum to form a porous polyvinylidene fluoride support layer; 5 μl of the in-situ filling layer polymerization precursor solution was injected into the porous polyvinylidene fluoride support layer and attached to the lithium negative electrode. 1.3 Al 0.3 Ti 1.7 5 μl of in-situ filling layer polymerization precursor liquid was dripped onto the other side of (PO4)3 and a lithium iron phosphate positive electrode was attached. The filling layer precursor liquid on the positive electrode surface only served as an interface wetting agent. The battery was sealed and left to stand at room temperature for 24 h to complete the polymerization and curing of the in-situ filling layer precursor liquid to obtain the interface-modified Li 1.3 Al 0.3 Ti 1.7 (PO4)3-based solid-state lithium battery.
[0050] Figure 2 This is a SEM image of the porous polyvinylidene fluoride support layer modified on the surface of the electrolyte sheet in Example 1. It can be seen from the figure that after the non-solvent phase separation process, Li 1.3 Al 0.3 Ti 1.7 A uniform 5μm thick porous support layer was formed on the (PO4)3 surface.
[0051] Figure 3 The optical photographs are of the in-situ filling layer polymerization precursor liquid before and after curing used in Example 1. It can be seen from the figure that after curing, the precursor liquid no longer has fluidity and exhibits good solid characteristics.
[0052] Example 2
[0053] The preparation method of the oxide electrolyte-negative electrode interface modification layer and the solid-state lithium battery provided in this embodiment refers to Example 1, with the main difference being that in the preparation of the porous support layer polymer solution, the polymer is polyvinylidene fluoride-hexafluoropropylene, and the low boiling point solvent is tetrahydrofuran.
[0054] Example 3
[0055] The preparation method of the oxide electrolyte-negative electrode interface modification layer and the solid-state lithium battery provided in this embodiment refers to Example 1, the main difference being that the oxide electrolyte is selected as garnet-type Li 6.4 Ln3Z 1.4 Ta 0.6 O 12 .
[0056] Example 4
[0057] The preparation method of the oxide electrolyte-negative electrode interface modification layer and the solid-state lithium battery provided in this embodiment refers to that in Example 1, the main difference is that in the preparation of the in-situ filling layer polymerization precursor solution, 1,3-dioxane is selected as the ether-based monomer.
[0058] Comparative Example 1
[0059] The preparation method of the oxide electrolyte-negative electrode interface modification layer and the solid-state lithium battery provided in this comparative example refers to Example 1, with the main difference that: in the preparation of the in-situ filling layer polymerization precursor solution, no initiator zinc trifluoromethanesulfonate is added, and finally the electrolyte filling porous support layer interface modification Li 1.3 Al 0.3 Ti 1.7 (PO4)3-based solid-state lithium battery.
[0060] Comparative Example 2
[0061] The preparation method of the oxide electrolyte-negative electrode interface modification layer and the solid-state lithium battery provided in this comparative example refers to Example 1, with the main difference being that no porous support layer is constructed on the surface of the oxide electrolyte, and only the electrolyte in Comparative Example 1 is used as the interface modification wetting agent between the oxide electrolyte and the positive and negative electrodes.
[0062] Figure 4 The solid-state lithium battery cycle performance test diagrams of Example 1, Comparative Example 1, and Comparative Example 2 are shown in the figure. It can be seen from the figure that: (1) the solid-state lithium battery assembled in Example 1 has a capacity retention rate of 92% after 400 cycles at room temperature and 0.5C; (2) in Comparative Example 1, since the filling layer is only the electrolyte, the stability of the lithium negative electrode is limited and side reactions will occur slowly. The capacity retention rate of the assembled battery after 300 cycles at room temperature and 0.5C is 65.7%; (3) in Comparative Example 2, since there is no porous support layer to hold the Li 1.3 Al 0.3 Ti 1.7 (PO4)3 is isolated from the lithium negative electrode, and continuous side reactions will occur when the electrolyte and the lithium negative electrode are in direct physical contact. The capacity retention rate of the battery is 42.6% after 300 cycles at room temperature and 0.5C.
[0063] Although the content of the present invention has been described in detail through the above preferred embodiments, it should be appreciated that the above description should not be considered as a limitation of the present invention. After reading the above content, it will be apparent to those skilled in the art that various modifications and substitutions of the present invention will occur. Therefore, the protection scope of the present invention should be limited by the appended claims.
Claims
1. An oxide electrolyte-negative electrode interface modification layer, characterized in that: The oxide electrolyte-negative electrode interface modification layer is located between the oxide electrolyte and the negative electrode, and is composed of a porous support layer and an in-situ filling layer; in: The porous support layer is formed by a low boiling point solvent in a polymer solution dripped onto the surface of the oxide electrolyte through non-solvent phase separation with moisture in humid air at a relative humidity of >80% RH on the surface of the solution; The in-situ filling layer is formed by infiltrating the porous support layer with a polymerization precursor liquid containing an ether monomer, a plasticizer, an initiator, and a lithium salt and then curing it in-situ.
2. The oxide electrolyte-negative electrode interface modification layer according to claim 1, characterized in that: The porous support layer has a pore size of 0.1-10 μm, preferably 1-5 μm, and a porosity of 30-70%, preferably 40-60%; the oxide electrolyte-negative electrode interface modification layer has a thickness of 2-10 μm, preferably 3-6 μm.
3. The oxide electrolyte-negative electrode interface modification layer according to claim 1 or 2, characterized in that: Taking the total mass of the oxide electrolyte-negative electrode interface modification layer as 100%, the mass of the porous support layer accounts for 30-50%, and the mass of the in-situ filling layer accounts for 50-70%.
4. The oxide electrolyte-negative electrode interface modification layer according to any one of claims 1 to 3, characterized in that: The ionic conductivity of the oxide electrolyte-negative electrode interface modification layer is not less than 10 -4 S / cm.
5. The oxide electrolyte-negative electrode interface modification layer according to any one of claims 1 to 4, characterized in that: The polymer for preparing the porous support layer is at least one of polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene, polymethyl methacrylate, and polyacrylonitrile, preferably at least one of polyvinylidene fluoride and polyvinylidene fluoride-hexafluoropropylene; The low boiling point solvent is at least one of acetone, tetrahydrofuran, xylene, diethyl ether and acetonitrile, preferably at least one of acetone and tetrahydrofuran.
6. The oxide electrolyte-negative electrode interface modification layer according to any one of claims 1 to 5, characterized in that: The ether monomer contained in the polymerization precursor liquid for preparing the in-situ filling layer is at least one of 1,3-dioxolane, 1,3-dioxane, trioxymethylene, and tetrahydrofuran, preferably 1,3-dioxolane; The plasticizer is at least one of fluoroethylene carbonate, dimethyl carbonate, ethyl methyl carbonate, diethyl carbonate, and propylene carbonate, preferably fluoroethylene carbonate; The initiator is at least one of zinc trifluoromethanesulfonate, tin trifluoromethanesulfonate, magnesium trifluoromethanesulfonate, scandium trifluoromethanesulfonate, and aluminum trifluoromethanesulfonate, preferably zinc trifluoromethanesulfonate; The lithium salt is at least one of lithium bis(trifluoromethanesulfonyl imide), lithium bis(pentafluoroethylsulfonyl imide) and lithium trifluoromethanesulfonate, preferably lithium bis(trifluoromethanesulfonyl imide).
7. The oxide electrolyte-negative electrode interface modification layer according to any one of claims 1 to 6, characterized in that: The volume ratio of the ether monomer to the plasticizer is 99:1-50:50, preferably 80:20-55:45; the amount of initiator added is 1-10mM of the total volume of the ether monomer and the plasticizer, preferably 3-9mM; the amount of lithium salt added is 0.5-2M of the total volume of the ether monomer and the plasticizer, preferably 0.8-1.2M.
8. The oxide electrolyte-negative electrode interface modification layer according to any one of claims 1 to 7, characterized in that: The oxide electrolyte is at least one of NASICON-type oxide, garnet-type oxide, and perovskite-type oxide; The NASICON-type oxide includes Li 1+x Al x M 2-x (PO4)3、Li 1+x+y Al x M 2-x Si y P 3-y O 12 , M is Ti or Ge, 0≤x≤0.5, 0≤y≤0.5, preferably Li 1+x Al x Ti 2-x (PO4)3, 0.2≤x≤0.4; The garnet-type oxide includes Li 7-x LqCy 2-x N x O 12 , N is Nb, Sb or Ta, 0≤x≤0.8, preferably Li 7- x LqCy 2-x Ta x O 12 , 0.4≤x≤0.6; The perovskite oxide includes Li 3x La 2 / 3-x TiO3, 0.06≤x≤0.14, preferably x=0.
11.
9. A method for preparing an oxide electrolyte-negative electrode interface modification layer according to any one of claims 1 to 8, characterized in that: The preparation method comprises the following steps: (1) dissolving a polymer in a low boiling point solvent to form a polymer solution and dripping it onto the surface of the oxide electrolyte, wherein the polymer solution is separated from water by a non-solvent phase in humid air at a relative humidity of more than 80% RH, and then dried to obtain a porous support layer; (2) An ether monomer, a plasticizer, an initiator, and a lithium salt are mixed to form a polymerization precursor solution, and the mixture is dripped into the porous support layer to wet the pores thereof, and the mixture is allowed to stand at room temperature under sealing conditions to perform in-situ curing to form an in-situ filling layer of a gel electrolyte, thereby obtaining the oxide electrolyte-negative electrode interface modification layer.
10. A solid-state lithium battery, characterized in that: The solid-state lithium battery comprises a positive electrode, a negative electrode, an oxide electrolyte, and an oxide electrolyte-negative electrode interface modification layer according to any one of claims 1 to 8; After modifying the porous support layer on one side of the oxide electrolyte, the polymerization precursor liquid of the in-situ filling layer is injected into the porous support layer, the negative electrode is attached, and the polymerization precursor liquid is dripped on the other side of the oxide electrolyte, the positive electrode is attached, sealed, and left to stand at room temperature to obtain the solid-state lithium battery.
Citation Information
Patent Citations
Salt-coated polymer interfacial protective layer on solid electrolyte surface and its preparation method
CN114006033B
Garnet type solid electrolyte interface modification method and application thereof
CN116799290A
